Methylfluorenes, methyldibenzofurans and methyldibenzothiophenes in oils and organic matter of West Siberia source rocks; The 23rd International Meeting on Organic Geochemistry, Torquay, England, 9-14 september 2007 - Goncharov I. V. Ivan Vasilyevich; Oblasov N. V.; Samoylenko V. V.; Nosova S. V. (2007, 2007)
В фонде НТБ ТПУ отсутствует